Role of Technology in Music Education - Dr. Sangeeta (Innovative Research Thoughts, 2017)
Information and communication technology (ICT) applications” in various fields of human endeavour, including education, appear to represent a paradigm shift away from the normal traditional concepts of operations and toward more refined and transformational processes, which is being greeted with great enthusiasm. “The social, political, religious, economic, and technical transformations that have occurred over the last several decades have made education and training for everyone more important than ever. However, educational systems around the world, to varying degrees, are struggling to provide equal educational opportunities for all, to equip their human resources with the knowledge and skills necessary for capacity building in rapidly changing economies and sophisticated living environments, and to prepare citizens for lifelong learning.